Awareness, practices and perceptions of community pharmacists towards antimicrobial resistance and antimicrobial stewardship in Libya: a cross-sectional study - Hiba A. Al-Shami; Usman Abubakar; Maryam S. E. Hussein; Hanin F. A. Hussin; Sondos A. Al-Shami (Taylor & Francis Group, 2023)
Abstract Background Community pharmacists play a vital role in promoting appropriate use of antibiotics in the community. This study evaluated the practices and perceptions of community pharmacists towards antibiotic use, antibiotic resistance, and antimicrobial stewardship in Libya. Methods A cross-sectional study was conducted among community pharmacists in Libya using a 47-item validated, pre-tested online questionnaire. Data was collected from December 2021 to February 2022 and was analysed using descriptive and inferential analyses. Results Of the 114 questionnaires included in the analysis, 54.4% were females, 78.1% had < 10 year working experience (78.1%), and 81.6% had a Bachelor of Pharmacy. Most (78.1%) strongly agreed/agreed that community pharmacists have an important role to play to reduce antibiotic resistance. Overall, the participants had a moderate perception towards antimicrobial resistance (median score: 21.5; IQR [16-28] out of 35.0). More than 40% supply antibiotics when patients requested them specifically, because if they do not supply them, patients will just go to another pharmacy. About 47% strongly agreed/agreed that if a patient cannot afford a full course of antibiotics all in one go, they will give them a smaller amount that they are able to afford at that time, even when a longer duration of treatment is required. Most (66.7%) had no previous involvement in antibiotics awareness campaign due to 'I have never heard about the campaign' (48.7%) and 'I do not have enough time to participate' (22.4%). Overall, the perception towards antimicrobial stewardship was good (20 [13-25] out of 25.0). Raising awareness of rational antibiotic use, including antimicrobial resistance, among pharmacy students (83.4%) and patient education by pharmacists in community pharmacies at the time medicines are supplied to patients (81.6%) were the most common strategies to improve rational use of antibiotics in community pharmacy. Conclusions Community pharmacists in Libya recognise their role in reducing antimicrobial resistance. They had a moderate perception towards antimicrobial resistance and a good perception towards antimicrobial stewardship. However, inappropriate antibiotic practices were common. The most common strategies to improve rational use of antibiotics in community pharmacy were raising awareness about the rational antibiotic use among pharmacy students and patient education by community pharmacists at the time antibiotics are dispensed to patients. Regulations are needed to restrict dispensing antibiotics without prescription among community pharmacists.